Experimental analysis of fin and tube heat exchanger in heating and cooling mode - Rubcov, Artur; Paulauskaitė, Sabina; Misevičiūtė, Violeta (International Conference “Environmental Engineering”, 2017)
The paper provides the results of experimental tests of a wavy fin and tube heat exchanger used to heat (cool) air in a ventilation system when the wavy fin of the heat exchanger is dry and wet. The experimental tests, performed in the range of 1000
Keywords: Air-to-water heat exchanger; wavy fin; dry surface of the fin; wet surface of the fin; heat transfer coefficient; air-to-water heat exchanger